Analysis of Nutritional Patterns and Preeclampsia During Pregnancy on the Incidence of low birth weight (LBW) - Dasimah; Riza Tsalasatul Mufida; Miftakhur Rohmah; Retno Palupi Yonni Siwi (Universitas STRADA Indonesia, 2024)
Every year in developing countries, approximately 20 million babies are born with low birth weight and 13 million babies are born with growth disorders in the womb. The high infant mortality rate in Indonesia, namely 30 per 1000 live births, makes Indonesia rank fifth with the highest number of LBW in the world and the birth of babies with low birth weight is identified as the largest contributor to the infant mortality rate. This study aims to determine the analysis of nutritional patterns and preeclampsia during pregnancy on the incidence of LBW. This research uses this type of research analytical observational with research design cross-sectional. The population of this study was 150 post-partum mothers who had given birth at term, had pregnancy complications (CED/Preeclampsia) and gave birth in the delivery room at Merauke District Hospital from January 2021 – December 2022. Statistical test using chi square to find out the relationship between 2 variables. Research results from 150 respondents were obtained The nutritional pattern of respondents is at risk of developing CED, namely 87 respondents (58.0%), Most of the preeclampsia respondents were at risk of developing preeclampsia, namely 60 respondents (40.0%) and the majority of respondents' birth weight was LBW, namely 119 respondents (79.3%). Analysis using tests Chi-Square for KEK the results were obtained p = 0.002 (< 0.05) and preeclampsia was obtained p = 0.036 (< 0.05) so it can be concluded that there is a relationship between nutritional patterns and preeclampsia during pregnancy with the incidence of LBW in the Merauke District Hospital. Whether or not many pregnant women experience the nutritional status of pregnant women is also influenced by the performance of health service workers. For this reason, health workers, especially midwives, should continue to motivate through counseling and IEC as well as educating mothers about the incidence of LBW.